Pengaruh Size, Pad, Dan Kompleksitas Terhadap Kelemahan Pengendalian Intern Pemerintah Daerah (Studi Empiris Pada Kabupaten/Kota Di Provinsi D.I.Y. Pada Tahun 2009-2014) - Pamuji, Fahroni Arif; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2017)
The purpose of this study was to determine the effect size, PAD, and complexity to the weakness of internal control of local governments. The population in this study were five district / municipal governments in the province D.I.Y. The samples used were 48 reports the results of the district / city. Secondary data were obtained from the official website of BPS. Sampling technique used is purposive sampling. The analysis technique used is multiple linear regression analysis. These results indicate that the size and complexity does not significantly affect the internal control weaknesses, while the PAD significantly affect the internal control weaknesses.